Design and Development of a Website for Micro, Small, and Medium Enterprises (MSMEs) of Pekunden Pottery Craft Using the Extreme Programming Method - Mulyaningsih, Agustina; Gustalika, Muhamad Azrino (CV. Media Inti Teknologi, 2025)
Background: The rapid growth of digital technology drives Micro, Small, and Medium Enterprises (MSMEs) to adopt information systems to improve competitiveness. Pekunden Pottery MSME in Pemalang Regency relies on conventional marketing, which limits its ability to expand market reach and manage sales effectively.Aims: This study aims to design and develop a website for Pekunden Pottery MSME as a digital promotional platform, to facilitate online transactions, and to manage sales data effectively.Methods: This study applied the Extreme Programming (XP) methodology through planning, design, coding, and testing phases. The researchers used Blackbox Testing to validate the functionality against user requirements.Results: The developed website provides product promotion, online ordering, payment integration with Midtrans, and automated shipping cost calculation using the RajaOngkir API. Testing achieved a 97.29% success rate, confirming that the system meets functional requirements and operates reliably.Conclusion: The system supports the digital transformation of Pekunden Pottery MSME by improving online visibility, simplifying sales management, and strengthening competitiveness. This research contributes academically by demonstrating the effective application of XP in MSME website development, while practically providing a model that enhances operational efficiency and business growth in the digital economy era.